Estratégias de relativização nas variedades lusófonas - Camacho, Roberto Gomes [UNESP]; Bechara, Eli Nazareth [UNESP] (My University, 2011)
This paper, which examines restrictive and non-restrictive constructions in the Lusophone varieties, assumes that Portuguese has a set of relativization strategies that are recognized by typological linguistics as constructions that define related groups of languages. Thus, it is possible that these different strategies, when employed by the same linguistic system, not really constitute variants of the same syntactic variable but the speaker’s actual choices facing the necessity to perform different social and discursive functions.

Este trabalho, que examina as construções relativas restritivas e não-restritivas nas variedades lusófonas, parte do princípio de que o português dispõe de um conjunto de estratégias de relativização que são reconhecidas na linguística tipológica como construções que definem grupos aparentados de línguas. Assim, é possível que essas diferentes estratégias, quando empregadas pelo mesmo sistema linguístico, não constituam realmente variantes de uma mesma variável sintática, mas escolhas reais do falante diante da necessidade de exercer diferentes funções discursivas e sociais.
Relativization strategies in the lusophone varieties
Keywords: Funcionalismo; Linguística Tipológica; Estratégias de Relativização; Functionalism; Typological Linguistics; Relativization Strategies